2008
DOI: 10.1101/gr.082701.108
|View full text |Cite
|
Sign up to set email alerts
|

Most mammalian mRNAs are conserved targets of microRNAs

Abstract: MicroRNAs (miRNAs) are small endogenous RNAs that pair to sites in mRNAs to direct post-transcriptional repression. Many sites that match the miRNA seed (nucleotides 2-7), particularly those in 3Ј untranslated regions (3ЈUTRs), are preferentially conserved. Here, we overhauled our tool for finding preferential conservation of sequence motifs and applied it to the analysis of human 3ЈUTRs, increasing by nearly threefold the detected number of preferentially conserved miRNA target sites. The new tool more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

57
6,362
8
78

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 7,571 publications
(6,505 citation statements)
references
References 40 publications
57
6,362
8
78
Order By: Relevance
“…The screen yielded miRNAs belonging to the miR‐125 and miR‐181 families, and their ability to modulate CBX7 was confirmed in a number of ways (O'Loghlen et al ., 2012). We subsequently took advantage of target prediction software ( targetscan and microRNA.org) (Betel et al ., 2008; Friedman et al ., 2009), which in addition to correctly predicting the target sites for miR‐125 and miR‐181 in CBX7 identified a potential target site for miR‐9 in the 3′UTR. Manual analysis identified a putative second target site for miR‐9 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The screen yielded miRNAs belonging to the miR‐125 and miR‐181 families, and their ability to modulate CBX7 was confirmed in a number of ways (O'Loghlen et al ., 2012). We subsequently took advantage of target prediction software ( targetscan and microRNA.org) (Betel et al ., 2008; Friedman et al ., 2009), which in addition to correctly predicting the target sites for miR‐125 and miR‐181 in CBX7 identified a potential target site for miR‐9 in the 3′UTR. Manual analysis identified a putative second target site for miR‐9 (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Their importance is underscored by the estimation that more than half of the human genes are regulated by miRNAs [1]. These small regulatory RNAs guide Argonaute effector proteins to target mRNAs via base-pairing, which in turn leads to destabilization of the target RNA and/or translational inhibition [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Any given miR may have hundreds of different mRNA targets (Friedman et al ., 2009). Although this study focuses on SIRT1 and TERT as targets of miR‐195, previous reports on SkMs have identified other targets such as AKT3, ADP ribosylation factor‐like protein 2, B‐cell lymphoma 2 (Bcl‐2), Ccnd, Cdc25, cyclin D1, cyclin E1, and FGF2 (Sekiya et al ., 2011; Sato et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%